A semi-empirical approach to evaluate the effect of constituent materials on mechanical strengths of GFRP mortar pipes. (February 2022) - Saghir, Farrukh; Gohari, Soheil; Moslemi, Navid; Abdi, Behzad; Mouloodi, Saeed; Burvill, Colin; Smith, Alan; Lucas, Stuart
Highlights: A semi-empirical approach based on the composition of constituent materials. The semi-empirical approach involves a comprehensive experimental program. Substantial experimental tests are conducted for various pipe categories. Overall improved design with cost-competitive outcomes. Abstract: Major constituents of glass fibre-reinforced polymer (GFRP) mortar pipes are high strength continuous and chopped fibres made up of E-CR (Electrical/chemical resistance) glass and particulate fillers in the form of silica sand, these are embedded in the thermoset matrix (vinyl ester resin). The main objective of current research is to better understand the individual and consolidated effect of constituent materials on mechanical strengths: axial and hoop tensile strengths of glass fibre reinforced polymer mortar pipes. A comprehensive experimental program (685 tests across 48 pipe categories) is completed towards evaluation of the axial and hoop tensile strengths, and composition of constituent materials using loss on ignition tests. The consolidated effects of constituent materials on mechanical strengths of GFRP mortar pipes are studied using a semi-empirical approach. This approach involved aligning the axial tensile ( σat ) and hoop tensile ( σht ) strength as a function of the composition of constituent materials: chopped glass (%), hoop glass (%), resin (%), and silica sand (%), and further applying this understanding to the formulation of semi-empirical prediction models to enable future GFRP composite designs to have a reduced design factor of uncertainty. The validation tests were carried out to check the predictive capability of the formulated semi-empirical prediction models. The magnitude of error percentage for predicted axial tensile strength is found to be less than 2.27%, while for hoop strength they are less than 1.13%. To better understand the dominant mode of failure that prevails under applied loading conditions, and to gain insight into the failure mechanisms, microscopic examination of failed surfaces was also performed using the scanning electron microscope (SEM). The semi-empirical prediction models presented in current research allows better understanding of the individual and consolidated effect of constituent materials upon the axial and hoop tensile strengths. This improved understanding provides guidance for practicing engineers, who depending upon the design requirements can use semi-empirical prediction models to selectively reinforce GFRP mortar pipes to have a custom-designed product.